Upgrades and maintenance of the CRYRING@ESR electron cooler for improved internal electron target operation - Koutsostathis, Athanasios; Krantz, Claude; Hanu, Elena-Oana; Herfurth, Frank; Heß, Regina; Kaufmann, Wolfgang; Lestinsky, Michael; Looshorn, Mirko Dieter; Menz, Esther Babette; Reiter, Andreas; Roßbach, Jon; Schippers, Stefan; et al. (HNPS Advances in Nuclear Physics, 2025)
The electron cooler of the CRYRING@ESR storage ring at the GSI-FAIR accelerator complex is a unique instrument, which not only provides beam cooling of the stored ions, but also serves as a low-energy electron target for Dielectronic Recombination experiments. The minimisation of vacuum contamination and the response to rapid energy changes are key requirements of the cooler in electron target mode. Therefore, a test bench was prepared to study the outgassing behaviour of the electron gun components and a setup was constructed to evaluate the drift-electrode-modulation of the acceleration voltage of the cooler. The vacuum studies showed that the electron gun cathode was severely malfunctioning and resulted in its replacement. The drift-electrode-modulation of the acceleration voltage showed significant improvements compared to direct modulation of the terminal voltage of the cooler.